Dissecting the Role of AXL in Cancer Immune Escape and Resistance to Immune Checkpoint Inhibition - Engelsen, Agnete S. T.; Lotsberg, Maria L.; Abou Khouzam, Raefa; Thiery, Jean-Paul; Lorens, James B.; Chouaib, Salem; Terry, Stéphane (Frontiers in Immunology, 2022)
The development and implementation of Immune Checkpoint Inhibitors (ICI) in clinical oncology have significantly improved the survival of a subset of cancer patients with metastatic disease previously considered uniformly lethal. However, the low response rates and the low number of patients with durable clinical responses remain major concerns and underscore the limited understanding of mechanisms regulating anti-tumor immunity and tumor immune resistance. There is an urgent unmet need for novel approaches to enhance the efficacy of ICI in the clinic, and for predictive tools that can accurately predict ICI responders based on the composition of their tumor microenvironment. The receptor tyrosine kinase (RTK) AXL has been associated with poor prognosis in numerous malignancies and the emergence of therapy resistance. AXL is a member of the TYRO3-AXL-MERTK (TAM) kinase family. Upon binding to its ligand GAS6, AXL regulates cell signaling cascades and cellular communication between various components of the tumor microenvironment, including cancer cells, endothelial cells, and immune cells. Converging evidence points to AXL as an attractive molecular target to overcome therapy resistance and immunosuppression, supported by the potential of AXL inhibitors to improve ICI efficacy. Here, we review the current literature on the prominent role of AXL in regulating cancer progression, with particular attention to its effects on anti-tumor immune response and resistance to ICI. We discuss future directions with the aim to understand better the complex role of AXL and TAM receptors in cancer and the potential value of this knowledge and targeted inhibition for the benefit of cancer patients.